ANALISIS KELEMAHAN EKSPLANASI MAHASISWA KAITANNYA DENGAN BUDAYA KERJA DAN PENGEMBANGAN KECERDASAN INTER-INTRAPERSONAL DALAM PERKULIAHAN ELEKTROMETRI (Universitas Negeri Semarang, 2014)
This study aims to gain an overview of student weakness in explanation of procedures, symptoms observed, and the basic concepts in the lecture of electrometry based laboratory activities associated with the work culture and the development of inter-intrapersonal intelligence. This study used 30 subjects, they are chemistry education students who take courses in analytical chemistry lab instruments. Data were collected through preliminary tests in writing and oral questions during student reported observational data. The mean value for the explanation of the procedure, the symptoms observed, as well as the basic concepts are respectively 60, 61 and 59 (score 100). Practicum that lasts to this day do not give opportunity to develop inter-intrapersonal ability students such as information identification, information elaborating, discussions to develop and evaluate procedures, formulate new concepts and create reports. Therefore it is necessary to built the electrometry lecture-based lab activities that give students the opportunity to develop inter-intrapersonal intelligence which is also associated with the work culture of Java.Keywords: Electrometry, Inter-intrapersonal, Lab Activity, Work Culture